KUALITAS PENYAMPAIAN KHOTBAH DI GEREJA: Peran Komunikasi Verbal dan Nonverbal dalam Meningkatkan Keterlibatan Jemaat - Aturut, Klisti; Ruindungan, Leo Mardani; Pohan, Juan Erwin (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2024)
This study focuses on the quality of sermon delivery at the Independent Congregational Fellowship (ICF) Korampotan Pondan, aiming to understand the congregation’s perception of the effectiveness of verbal and non-verbal communication used by the preacher. The quality of sermon delivery plays an essential role in building the congregation’s engagement and understanding of spiritual messages, particularly for older congregants. This research employed a quantitative method with a survey approach, involving 95 randomly selected respondents. Data were collected through a questionnaire using a Likert scale and analyzed descriptively. The results indicate that congregants responded positively to aspects of voice clarity, intonation, and sermon duration, which were considered effective in maintaining their attention. On the non-verbal side, the preacher’s authoritative appearance, use of hand gestures, and eye contact were also seen as supporting emotional connection and preacher credibility. However, there remains a need to enhance the relevance of sermon content to the daily lives of the congregation. These findings contribute to an understanding of the importance of adjusting sermon communication methods based on the characteristics of the congregation and are expected to serve as a foundation for developing communication skills in church ministry.